El uso de redes sociales para la contratación de capital humano en las empresas del cantón Salcedo. - García Moreno, Gabriel Alejandro. (2023)
This research is to propose using social networks as a support tool for recruiting human capital in companies in the canton of Salcedo. Traditional recruitment practices need to be more efficient, and the effects of globalization require the generation of changes in all organizational areas to face the competition. Companies must be present in technology, build their brand image, and recruit potential candidates. For this, they need to design strategies in social networks that allow them to optimize resources. A quantitative methodology was used for this project, with the survey as a support instrument and, in addition to the tabulation, QFD matrices were developed, which made it possible to find out the current situation of the companies concerning the use of social networks in the recruitment of human capital. For this, the contribution as a working team is to propose social networks as support tools to optimize recruiting and hiring human capital, describing the impacts they cause in society and the business world. Social networks are bidirectional tools that must be used responsibly, knowing in depth the benefits they have and thus will be available to companies for continuous improvement.